A novel hybrid iron-calcium catalyst/absorbent for enhanced hydrogen production via catalytic tar reforming with in-situ CO2 capture. (1st April 2020) - Han, Long; Liu, Qi; Zhang, Yuan; Lin, Kang; Xu, Guoqiang; Wang, Qinhui; Rong, Nai; Liang, Xiaorui; Feng, Yi; Wu, Pingjiang; Ma, Kaili; Xia, Jia; et al.
Abstract: An iron-calcium hybrid catalyst/absorbent (Ca–Al–Fe) is developed by a two-step sol-gel method to enhance tar conversion, cyclic CO2 capture and mechanical strength of absorbent for hydrogen production in calcium looping gasification. The developed catalyst/absorbent consists of CaO and brownmillerite (Ca2 Fe2 O5 ) with mayenite (Ca12 Al14 O33 ) as inert support. Comparing with three candidate absorbents without Ca2 Fe2 O5 or Ca12 Al14 O33, cyclic carbonation reactivity and mechanical strength of Ca–Al–Fe are largely promoted. Meanwhile, Ca–Al–Fe approaches the maximum conversion rate of 1-methyl naphthalene (1-MN) with enhanced hydrogen yield around 0.15 mol/(h·g) under reforming conditions of present study. Ca–Al–Fe also shows the largest CO2 absorption and lowest coke deposition. Influences of operation variables on 1-MN reforming are evaluated and recommended conditions can be iron to CaO mass ratio of 10%, reaction temperature of 800 °C and steam to carbon in 1-MN mole ratio of 2.0. Ca–Al–Fe hybrid catalyst/absorbent presents good potential to be applied in future. Highlights: A novel Ca–Al–Fe hybrid catalyst/absorbent was synthesized by a two-step sol-gel method. Brownmillerite and mayenite were integrated to CaO and kept stable after reforming. Cyclic CO2 capture reactivity and mechanical strength are largely promoted. Novel material presented maximum tar conversion and efficient H2 production. Operation conditions had significant influences on tar catalytic conversion.